Indian culture, lunar phases and stock market returns. (29th January 2020) - Lingaraja, Kasilingam; Paul, Justin; Selvam, Murugesan
Return from the Indian stock market has been very attractive for investors from around the world during the last decade. Taking into account the importance of this emerging market, we examine the relation between lunar phases (full moon and new moon days) and the stock market returns from India, linking with Indian culture. Moon has a natural power which plays a significant role in phenomena of nature and also on human behaviour and stock market returns. The main purpose of the study is to examine the lunar effect on the stock markets and to test the normality and volatility of daily returns. Five major sectoral indices from the National Stock Exchange (NSE) were selected to investigate the relation between lunar phases and the stock market returns. Statistical tools like descriptive statistics, GARCH (1, 1) model and Granger causality were used to test the hypothesis and fulfil the objectives of this study. The results imply that the moon cycle affects individual mood and thinking process and leads to stock market volatility. The findings of this study would help the investors to formulate investment strategies to earn expected returns in the market.